Pengaruh Kepuasan Konsumen, Label Halal, Citra Merek, Kualitas Produk, dan Pengalaman Konsumen Terhadap Loyalitas Kosmetik Merek Wardah Di Yogyakarta (Bisman (Bisnis dan Manajemen): The Journal of Business and Management, 2022)
This research purpose to examine the effect of consumer satisfaction, halal label, brand image, product quality and consumer experience on the loyalty of Wardah cosmetics brand in Yogyakarta and to determine the simultaneous effect of X1, X2, X3, X4 and X5. This research was conducted in Yogyakarta in August 2022. This research is a quantitative study with 120 respondents. The data collection technique was one by means of a questionnaire. The analytical technique used in this research is multiple linear regression analysis. Based on the result, it is obtained a regression eqution of : Y= 0,742 + 0,193 X1 + 0,333 X2 + 0,293 X3 +0,175 X4 + 0,272 X5. The results of this study prove that Consumer Satisfaction has a positive and significant effect on Brand Loyalty, Halal Label have a positive and significant effect on Brand Loyalty, Brand Image has a positive and significant effect on Brand Loyalty, Product Quality has a positive and significant effect on Brand Loyalty and Consumer Experience has an effect positive and significant to Brand Loyalty. Consumer Satisfaction, Halal Label, Brand Image, Product Quality and Consumer Experience simultaneously have a significant effect on Brand Loyalty with an F-count value of 27,918 and a significant value of 0,000. The results of the analysis obtained that the Adjusted R Square value 53,1% means that the effect of Consumer Satisfaction, Halal Label, Brand Image, Product Quality And Consumer Experience on Brand Loyalty contributes 53,1%. While the remaining 46,9% is influenced by other factors outside the study.